2015
DOI: 10.1016/s0924-9338(15)30634-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Aberrant Salience, Psychotic Symptoms and Pharmacological Treatment in a Follow-up Study: is the Salience a Lifetime Trait?

Abstract: Introduction: Aberrant salience is the incorrect assignment of salience, significance or value to different innocuous stimuli. It seems closely related with dysregulation of the dopamine system that in turn relates with proneness to develop psychosis. Objectives: To evaluate aberrant salience processing in a clinical trans-diagnostic sample, its relationship with anamnestic psychotic symptoms and current psychopathology, and possible variations of aberrant salience after three months of clinical-based treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The assessment of aberrant salience in people with prodromal and full-blown psychotic symptoms might well be a noteworthy clinical tool both for diagnostic and prognostic purposes (Lucia Godini et al, 2015).…”
Section: The Aberrant Saliencementioning
confidence: 99%
“…The assessment of aberrant salience in people with prodromal and full-blown psychotic symptoms might well be a noteworthy clinical tool both for diagnostic and prognostic purposes (Lucia Godini et al, 2015).…”
Section: The Aberrant Saliencementioning
confidence: 99%
“…In the last decade there has been an increase in data regarding salience alterations and their relevance to psychosis psychopathology (Godini et al ., 2015; Kapur, 2003). Salience is not a new concept; the observation and description of some of the features associated with this entity date back to Jaspers and Conrad (Mishara, 2010; Mishara & Fusar‐Poli, 2013; Sass & Ratcliffe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One such measure is the Aberrant Salience Inventory (Cicero et al, 2010). In a recent follow-up study, Godini et al (2015) found it to be associated with the lifetime presence psychotic symptoms, and not with a reduction in psychotic symptoms after pharmacological treatment. Recently, the Personality Inventory for the DSM-5 (PID-5; Krueger et al, 2012) was developed in accordance with the criterion B of the Alternative Model on Personality Disorders.…”
mentioning
confidence: 99%